The signal-to-noise ratio assessment in cochlear implanted patients through the Italian Matrix Sentence test (Oldenburg test). (3rd April 2019) - Gallo, Samanta; Castiglione, Alessandro
Abstract: Purpose: A lot of energy has been spent in advances in audiology to define a new strategy of diagnosis and rehabilitation in hearing-impaired patients, in particular for those rehabilitated with cochlear implants or hearing aids. The OLSA test or Matrix Sentence test is a new testing tool able to precisely define a signal-to-noise ratio in different clinical or diagnostic conditions. Spreading of this new test has a standardized level of reference which can help clinicians in comparing patients and data. Method: Implanted patients with contralateral hearing aid use were enrolled in the recent Italian Matrix Sentence test validated for the Italian language. Patients with good perceptual outcomes without post-operative complications were asked to undergo the Italian Matrix Sentence test twice in a day section with or without a cochlear implant and/or contralateral hearing aids. Results: Forty-five cochlear implanted patients with good outcomes and without major complications were enrolled in the present study to compare speech discrimination in noise with cochlear implants and/or hearing aids during bimodal or unimodal stimulation. Obviously, a significant difference was noticed in patients with cochlear implants or hearing aids when compared with patients without digital devices, as well as a statistically significant difference was found in patients with a cochlear implant only when compared with patients with hearing aids. Nevertheless, significant differences were found when comparing bimodal stimulation to unimodal stimulation with the cochlear implant: an ameliorative trend has been reported among patients with either the devices (hearing aids and cochlear implant). Conclusion: The Italian Matrix Sentence test is useful and automated speech audiometry allows a comprehensive evaluation of perceptual abilities in hearing impaired patient. Nevertheless, gives important information among implanted patients especially in the adaptive mode for central comprehension of the signal in noise.